Peramalan Penerimaan Pajak Negara Indonesia Tahun 2019 Menggunakan Metode Pemulusan Eksponensial Ganda Tipe Brown - Yatri Asri; Dony Permana (UNIVERSITAS NEGERI PADANG, 2019)
Abstract – Taxes are potential source of funds from the people and are used to build infrastructure and advance the economy of a country. The Calculation of estimated tax revenue targets that do not exactly have an effect on the various planned program activities. This research used the data of Indonesia tax revenue that obtained from Central Agency on Statistics Republic of Indonesia. This research aims to predict Indonesian tax revenue in 2019 using double exponential smoothing type Brown. The result of data processing obtained the forecast value of Indonesia tax revenue in 2019 using double exponential smoothing type Brown is IDR 1,734,847 billion. Keywords: Tax, Forecasting, Exponential Smoothing Type Brown Method